Extrato de Alecrim (Rosmarinus officinalis L.): Um antioxidante eficiente para uso no biodiesel - Medeiros, Maria Lins de (2013)
Biodiesel is susceptible to oxidative processes due to several factors, including the presence of oxygen, heat, light, enzymes, trace of metals, among others. Oxidation stability is an important quality criterium for biodiesel. The literature reports surveys of natural and synthetic antioxidants added to biodiesels from various sources, in order to increase the oxidative stability and thus the lifetime thereof. Beyond this, it provides reducing emissions of toxic gases. In this study, rosemary extracts and synthetic antioxidants were used to retard the oxidation of methyl biodiesel cotton (BA). This biodiesel was additive and stored in carbon steel tanks. During storage, the better oxidative stability was observed, for the biodiesel with the addition of TBHQ and the addition of the mixture of rosemary extract and TBHQ. These antioxidant formulations protected the biodiesel for 90 days, while the ethanol extract of rosemary protected for 60 days and the synthetic antioxidant BHT has not fulfilled the parameters established by ANP. The ethanol extract of rosemary can be considered promising to maintain the quality of biodiesel. Furthermore, the thermal profile obtained by thermogravimetric analysis showed that the ethanolic extract of rosemary may be considered a heat stable since it shows a loss of mass, above 190 ° C.